Creating a classroom community of young scientists : a desktop companion - Bloom, Jeffrey W. (Canada : Irwin publishing, 1998)
Offering an approach to teaching science, this work is intended to help teachers - both pre-service and in-service - develop science programs in their classrooms. It provides an approach that aims to capture children's imaginations, stimulate their curiosity, and create a foundation for their interest in science and the world in which they live.
Includes index.
Keywords: Science -- Study and teaching (Elementary); Science -- Experiments; Sciences -- Étude et enseignement (Primaire)